Thermal impacts of basaltic lava flows to buried infrastructure: workflow to determine the hazard - Sophia W. R. Tsang; Jan M. Lindsay; Ben Kennedy; Natalia I. Deligne (Journal of Applied Volcanology, 2020)
Abstract Lava flows can cause substantial physical damage to elements of the built environment. Often, lava flow impacts are assumed to be binary, i.e. cause complete damage if the lava flow and asset are in contact, or no damage if there is no direct contact. According to this paradigm, buried infrastructure would not be expected to sustain damage if a lava flow traverses the ground above. However, infrastructure managers (“stakeholders”) have expressed concern about potential lava flow damage to such assets. We present a workflow to assess the thermal hazard posed by lava flows to buried infrastructure. This workflow can be applied in a pre-defined scenario. The first step in this workflow is to select an appropriate lava flow model(s) and simulate the lava flow’s dimensions, or to measure an in situ lava flow’s dimensions. Next, stakeholders and the modellers collaborate to identify where the lava flow traverses buried network(s) of interest as well as the thermal operating conditions of these networks. Alternatively, instead of direct collaboration, this step could be done by overlaying the flow’s areal footprint on local infrastructure maps, and finding standard and maximum thermal operating conditions in the literature. After, the temperature of the lava flow at the intersection point(s) is modelled or extracted from the results of the first step. Fourth, the lava flow-substrate heat transfer is calculated. Finally, the heat transfer results are simplified based on the pre-identified thermal operating conditions. We illustrate how this workflow can be applied in an Auckland Volcanic Field (New Zealand) case study. Our case study demonstrates considerable heat is transferred from the hypothetical lava flow into the ground and that maximum operating temperatures for electric cables are exceeded within 1 week of the lava flow front’s arrival at the location of interest. An exceedance of maximum operating temperatures suggests that lava flows could cause thermal damage to buried infrastructure, although mitigation measures may be possible.